Effect of paddle grip on segmental fluid distribution and injuries occurrence in elite slalom paddlers - Baláš, J.; Bilý, M.; Coufalová, K.; Martin, A. J.; Cochrane, D. J. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: The aim of this current study was to assess the segmental fluid distribution, grip strength and injury occurrence in elite slalom kayakers and canoeists.